An investigation of stellite-6 alloy containing 5.0 wt% silicon - Kuzucu, V; Ceylan, M; Celik, H; Aksoy, I (Elsevier Science Sa, 1998)
Metal microscopy, X-ray diffraction, differential scanning calorimeter and hardness tests were used to examine and analyze the details of the microstructure of a cobalt based alloy with the composition Co-28Cr-5Si-4W-1.1C. The cast sample has a dendritic microstructure. Eutectic carbides such as M7C3, M23C6, M3C2, inter-metallic phases such as mu and sigma phases and some silicon compounds such as CrSi2, WSi2, CoSi2 solidify in the inter-dendritic regions. In the samples cooled in water and liquid nitrogen after annealing, some of the carbide phases and inter-metallic phases disperse in the dendritic grains, their hardnesses being found to be greater than the hardness of the cast sample. In addition, it is seen that the reverse martensitic or ordering transformations occur in the heating regime between 200 and 450 degrees C depending on the heat treatment applied to the samples. (C) 1998 Elsevier Science S.A. All rights reserved.
Keywords: stellite-6; silicon; microstructure; carbides; X-ray diffraction